BEST PRACTICE PELAYANAN ADMINISTRASI KEPENDUDUKAN KABUPATEN KUDUS - Listyaningsih Dewi Pamungkas; Rukhana Fitriati (Dialogue : Jurnal Ilmu Administrasi Publik, 2019)
This study aims to analyze the concept of best practice at the Population Administration and Civil Registration office of Kudus Regency. The study is implemented by applying the qualitative descriptive research methods. In terms of theoretical framework, the article refers to best practice theory. Best practice theory suggests criteria to examine policy innovation, namely impact, partnerships, sustainability, leadership, and innovations in local contexts that can be transferred (transferability). The results of this study indicate that the Population Administration and Civil Registry especially in the Civil Registry Population Service is categorized as good and feasible as a "Role Model of Public Service Provider" for other regions. The commitment of agency leadership in improving the quality of public services is commendable. In addition, the Kudus regency also provides facilitation and provides adequate infrastructure and facilities. The important finding of the research also relates to several other factors such as democratic leadership style; adequate human resource capacity; and the improved supply system of the E-KTP form from central government is among the factors that support the performance of population administration and civil registration services in Kudus Regency. On the other hand, there are factors interfering the performance of the admindukcapil. The factors are inadequate support of internet network in SIAK and unreliability of server. There is also a need to increase public awareness to complete population documents. In special cases, such as in time of national events such as election, demand for completion of population documents increased significantly.